A rede de proteção e enfrentamento da violência contra a pessoa idosa em Manaus: avanços e desafios - Meleiro, Maria Luiza De Andrade Picanço (2021)
The main objective of this dissertation was to analyze the existing articulation between the main institutions that integrate the protection network and the fight against violence against the elderly in the municipality of Manaus, identifying possible advances and challenges of this network, in the light of Law 12.461, of 26 July 2011, which made notification to the protection and coping network mandatory, in case of suspicion or confirmation of violence against the elderly. To this end, the legal frameworks and public policies related to the rights of the elderly were described in Brazil, in the state of Amazonas and in the city of Manaus; mapped the main institutions that make up the network to protect and confront violence against the elderly in the city of Manaus; and, the categories of violence suffered by the elderly were identified after the implementation of the law in the city of Manaus-AM and the notifications processed. A descriptive and structured study was carried out based on a quantitative and qualitative research. In the field of research, the managers of sixteen institutions that make up the protection network were heard. The survey concluded that there was no progress in addressing violence against the elderly after the law came into force, that the law is unknown and that the network is unaware of any progress in this regard. Professionals are afraid to notify, fear threats and possible involvement in legal proceedings. He also concluded that there are negligence, and the notification process is bureaucratic, but, above all, there is a lack of knowledge of this need, since there is a lack of guidance and awareness for the network as a whole. There are also structural issues that hinder the act of notifying, influenced by the specificities and the structures of the services, most of which are insufficient. There is no monitoring of the notifications made; the network does not know its consequences or interventions with abusers. The study also pointed out that there is no articulation between the safety net, so that the demands of the elderly receive adequate treatment and swift responses, just as there is no flow of care designed to care for the elderly, in the event of violence. It is hoped from the results of this study to contribute with information that may be relevant in order to assist, guide and / or direct the actions of the Network for the Protection and Facing of Violence against the Elderly, in the city of Manaus. The data, information and reflections recorded here can stimulate the debate and assist managers in better understanding the phenomenon of violence against the elderly, in the dynamics surrounding the network, as well as in understanding the aspects of reality that need some intervention. The results also lend themselves to subsidize managers, both public and private in the elaboration of public policies that can somehow mitigate the suffering and pain caused to this population.